Atypical employment and in-work poverty: a different story for part-timers and temporary workers? - Herman Deleeck Centre for Social Policy, Antwerp; Horemans, Jeroen (Antwerp, 2017)
"Both part-time and temporary employment have been shown to be associated with particular high poverty rates across Europe. Yet, theoretical arguments as to why this is the case remain scarce. Given the multifaceted nature of in-work poverty, the main aim of this chapter is unravel the different mechanisms that either cause or potentially limit the poverty risk of both groups of atypical workers. The results indicate that both groups are unable to secure a decent income to maintain themselves, not to mention their inability to sustain a family. However, their poverty risk remains remarkably limited when we take all income sources into account. We find that temporary and part-time workers tend to be protected against poverty differently. Government transfers are particularly important for temporary workers as they partially compensate periods out of work. Part-timers are more likely to rely on the earnings of other household members to avoid poverty, but with important differences across countries."